Positioning the Health Services Research Workforce for Continued Success: Recommendations from AcademyHealth Stakeholders. (21st September 2018) - Menachemi, Nir; Simpson, Lisa A.; Wolfe, Meghan J.
Abstract : AcademyHealth established a Workforce Initiative Task Force in 2016 to conduct an assessment of the state of the health services research workforce and develop recommendations for its future in the context of the changing health care and research ecosystems. This assessment included four components: a series of commissioned papers, an online priority setting process, a multistakeholder summit, and final analysis by the AcademyHealth Education Council. This paper presents this process and the resultant list of prioritized recommendations and planned next steps.